2019
DOI: 10.1016/j.ijom.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Extracraniofacial anomalies in craniofacial microsomia: retrospective analysis of 991 patients

Abstract: Craniofacial microsomia (CFM) is characterized by a unilateral or bilateral underdevelopment of the facial structures arising from the first and second pharyngeal arches, but extracraniofacial anomalies may be present. This retrospective study provides an overview of the prevalence and types of extracraniofacial anomalies in patients with CFM and studied the characteristics of patients with CFM and extracraniofacial anomalies. All patients diagnosed with CFM seen in four craniofacial centers were included. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 41 publications
1
42
0
1
Order By: Relevance
“…Furthermore, since many of these malformations can be oligo/asymptomatic, recognizing them early is essential. 15 The infant’s initial additional tests identified only vertebral anomalies, since the cranial CT, the echocardiogram, and the urinary tract ultrasound were normal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, since many of these malformations can be oligo/asymptomatic, recognizing them early is essential. 15 The infant’s initial additional tests identified only vertebral anomalies, since the cranial CT, the echocardiogram, and the urinary tract ultrasound were normal.…”
Section: Discussionmentioning
confidence: 99%
“…Extracraniofacial malformations, in turn, present a lower frequency, with prevalence ranging from 2-79% of patients with CFM, 15 and can include skeletal changes, malformations of the central nervous system, cardiovascular abnormalities, and, more rarely, anomalies of the urogenital tract, gastrointestinal tract, and respiratory system. 14 , 15 Some studies correlate larger craniofacial involvement with a higher frequency of extracraniofacial malformations. Furthermore, since many of these malformations can be oligo/asymptomatic, recognizing them early is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Renkema et al found that higher OMENS-Plus nerve and soft tissue scores and higher Pruzansky-Kaban classification scores were associated with an increased risk of extracraniofacial anomalies. 35 It seems logical that patients with more severely hypoplastic facial structures are at increased risk of ocular anomalies. However, none of the proposed aetiologies of CFM fully explain the combination of anomalies observed in the clinical spectrum of CFM, or the relationships between these anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Rib cartilage anomalies have been rarely reported. Spinal deformities may occur in isolation, as well as in association with multisystem malformations such as oculo-auriculo-vertebral spectrum (Beleza-Meireles et al, 2015;Renkema et al, 2019;OAVS). In order to better understand the association between microtia and thoracic deformities, the study just focuses on those with microtia and thoracic involvement and no other feature.…”
mentioning
confidence: 99%